Direct synthesis of (Fluoro)ketones from carboxylic acids and organozincs via acyloxyphosphonium ions - Jindal, Aanya (Kansas State University, 2024)
The thesis presented herein delineates a straightforward approach for the generation of ketones directly from carboxylic acids through the intermediacy of acyloxyphosphonium ions. The work presented herein builds upon research findings performed in the laboratory of my thesis advisor, Prof. Socrates B. Munoz that have been published as a pre-print dealing with the synthesis of both [alpha],[alpha]-difluoro as well as non-fluorinated ketones; the latter being the main focus of my work. However, an introduction on the significance of fluorine, Fluoroketones and non-fluorinated ketones in organic chemistry is also provided. Importantly, my work is focused on the application of the previously found method for Fluoroketones synthesis and its expansion to the synthesis of benzophenones, and a manuscript delineating the preparation of both types of ketones (fluorinated and non-fluorinated benzophenones) is currently under preparation for submission to peer-review in which I am a listed co-author along with various members of the Munoz lab. Of note, these electrophiles (i.e. acyloxyphosphonium ions) are easily accessible commodity chemicals which renders their use in synthetic organic chemistry as highly practical. The work delineated herein establishes the use of these electrophiles in Cu-catalyzed cross-coupling reactions with easy-to-generate organozinc reagents as carbon nucleophiles. These transformations lead to the efficient production of ketones in a facile and practical manner. The transformations take place under mild reaction conditions (ranging from 0°C to room temperature), allowing for the generation of target compounds in brief reaction intervals. In addition, the approach demonstrates remarkable chemoselectivity and compatibility with various functional groups, highlighting its effectiveness and versatility. In the case of benzophenones, several FDA-approved active pharmaceutical ingredients (APIs) have been established as suitable substrates and have been successfully derivatized into their corresponding ketones. Finally, this thesis concludes with our group’s collaborative efforts to elucidate the nature of active electrophiles in these transformations. Accordingly, the mechanistic investigations using both fluorinated as well as non-fluorinated benzoic acids through NMR spectroscopic studies are presented and discussed.
Keywords: Organofluorine chemistry; Benzophenone synthesis; Organozinc reagents; Acyloxyphosphonium ions